Clinical evaluation of a superabsorbent polymer dressing in enabling self-care of wounds. (2nd June 2020) - Barrett, Simon; Welch, Donna; Rippon, Mark G; Rogers, Alan A
Abstract : Patient involvement in their own treatment can enable those with wounds in the community to play an active role in the management of their condition by, for example, completing dressing changes between health professional visits. The original primary study was undertaken to assess the clinical effectiveness of Zetuvit Plus Silicone Border (ZPSB) on exudate management. This retrospective sub-group analysis is aimed to demonstrate the effectiveness of a superabsorbent polymer (SAP) dressing (ZPSB) in enabling patients or their carers to undertake unsupervised dressing changes on their own. ZPSB was found to be clinically effective in this subgroup of patients, while also having additional features that enabled the patient to self-care. Overall, ZPSB enabled the patient to be part of their treatment plan and play an active role in the care of their wounds, thereby promoting self-care. This had a positive effect on nursing time saving and patient satisfaction.